Multipath routing protocols for wireless multimedia sensor networks: a survey. (2018) - Chikh, Asma; Lehsaini, Mohamed
Recent advances in sensor networks have led to a new category of networks called wireless multimedia sensor networks (WMSNs). These networks can support a variety of multimedia applications that have more requirements than other kinds of applications in terms of latency, energy consumption and quality of service. However, routing protocols designed initially for sensor networks cannot fulfil these requirements specially those involving a single-path in the data delivery process. For this purpose, multipath routing protocols are considered as appropriated solutions to achieve these goals since they can efficiently reduce energy consumption, prolong network lifetime, reduce latency and enable load balancing. In this paper, we survey recent multipath routing protocols designed for WMSNs and present a general classification for the various approaches pursued. Moreover, we also compare them based on relevant metrics such as architecture, hole bypassing, path disjointness, load balancing, bandwidth aggregation, energy efficient, reducing delay and data reliability.